KESEHATAN MENTAL GURU PENDIDIKAN ANAK USIA DINI - Yudhiarti, Ndaru Putri (JOURNAL FASCHO : JURNAL PENELITIAN DAN PENDIDIKAN ANAK USIA DINI, 2021)
This study aims to determine the description of the mental health of PAUD teachers during the COVID-19pandemic in Ngawi Regency. This study uses descriptive quantitative research methods with the research population of all PAUD teachers in Ngawi district. The sample was determined by convenience sampling technique. The sample in this study amounted to 75 PAUD teachers. The data collection tool used is a mental health questionnaire. The results showed that the mental health level of PAUD teachers in Ngawi district was in the low category with a percentage of 4%, the medium category with a percentage of 25.3%, and the high category with a percentage of 70.7%. This shows that during the COVID-19pandemic, PAUD teachers in Ngawi district were able to manage mental health.